Strategic Foresight and Digital Transformation: A Dual Approach to Innovation - HOSNI , Feten (Revue Internationale des Sciences de Gestion, 2025)
This research aims to introduce a new concept of the relationship between digital transformation and strategic foresight by exploring how multidimensional digital transformation can improve companies’ foresight performance, which in turn positively impacts innovation capabilities. In this context, this research seeks to understand how digitalization can impact the practice of strategic foresight and the role it plays in developing innovation capabilities by identifying the means that can be adopted to develop strategic thinking about the future and respond to strategic changes. Data were collected from 10 Tunisian holdings companies through semi-direct interactions, non-participatory observation, and internal company documents, enabling us to introduce a new concept: the close link between digital transformation and foresight practice, such as collective anticipation. This study is challenging because it demonstrates the extent to which foresight practices have evolved and the extent to which digital transformation can impact performance and practice in companies located in a developing country.